1993
DOI: 10.1161/01.atv.13.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Additive and synergistic effects of a low-molecular-weight, heparin-like molecule and low doses of cyclosporin in preventing arterial graft rejection in rats.

Abstract: Arteriosclerotic intimal proliferation is one of the main long-term complications of organ transplantation. Low-molecular-weight, heparin-like molecules prevent myointimal proliferation in arterial wall injury and limit rejection in skin allografts. Cyclosporin limits rejection but has no major effect on intimal proliferation. Therefore, an experimental protocol was designed to test whether heparin-like molecules interacted with low doses of cyclosporin to prevent arterial wall immune system injury and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Here, we show that the preventive and curative effects of CsA on AAAs are paralleled with aortic wall VSMC accumulation. Those results are compatible with the fact that one hallmark of CsA-induced vasculopathy in organ transplantation is the inappropriate accumulation of VSMCs [29]. Most importantly, in our study, the blocking antibody strategy credit the notion that CsA-induced TGF-beta1 preserves and restores VSMC content in AAAs, while controlling inflammation and proteolysis.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we show that the preventive and curative effects of CsA on AAAs are paralleled with aortic wall VSMC accumulation. Those results are compatible with the fact that one hallmark of CsA-induced vasculopathy in organ transplantation is the inappropriate accumulation of VSMCs [29]. Most importantly, in our study, the blocking antibody strategy credit the notion that CsA-induced TGF-beta1 preserves and restores VSMC content in AAAs, while controlling inflammation and proteolysis.…”
Section: Discussionsupporting
confidence: 90%
“…Using aorta-allografted rats, Mennander et al 18 found a transient worsening of transplant arteriosclerosis by cyclosporin treatment; others found no effect 1719 or an inhibiting effect 20 that disappeared after discontinuation of the treatment. One explanation for this discrepancy could be that studies with either a worsening effect or no effect used the lowest doses of cyclosporin (2 mg/kg SC, 17 5 mg/kg PO, 18 or 5 mg/kg SC, 19 ), whereas the one study with a reducing effect used a higher dose of cyclosporin (10 mg/kg SC 20 ). The latter dose is similar to the 8 to 10 mg/kg IM used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, a protection of the vascular endothelium by heparin and heparin derivatives seems to be present. The effect upon transplant intimal hyperplasia has been demonstrated experimentally with low molecular weight heparin in combination with cyclosporine (Plissonnier et al 1992) and according to our own experience there are heparin derivatives without anticoagulant effects, which efficiently protect aorta grafts against development of intimal hyperplasia (Stafberg et al 1993). To our knowledge there are no clinical studies in transplanted patients with heparinlike substances presented as yet.…”
Section: Prevention and Treatment Of Cvrmentioning
confidence: 98%